2006
DOI: 10.1074/jbc.m604429200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fructose-1,6-bisphosphatase by Aminoimidazole Carboxamide Ribotide Prevents Growth of Salmonella enterica purH Mutants on Glycerol

Abstract: The enzyme fructose-1,6-bisphosphatase (FBP) is key regulatory point in gluconeogenesis. Mutants of Salmonella enterica lacking purH accumulate 5-amino-4-imidazole carboxamide ribotide (AICAR) and are unable to utilize glycerol as sole carbon and energy sources. The work described here demonstrates this lack of growth is due to inhibition of FBP by AICAR. Mutant alleles of fbp that restore growth on glycerol encode proteins resistant to inhibition by AICAR and the allosteric regulator AMP. This is the first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 54 publications
(47 reference statements)
1
29
0
Order By: Relevance
“…DM2 (purH355) is a representative purH mutant strain with a previously described frameshift mutation that eliminates all PurH activity in the cell (6). DM2 and other purH mutants of S. enterica required exogenous addition of the HMP moiety of thiamine to grow in glucose medium with adenine (3)(4)(5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DM2 (purH355) is a representative purH mutant strain with a previously described frameshift mutation that eliminates all PurH activity in the cell (6). DM2 and other purH mutants of S. enterica required exogenous addition of the HMP moiety of thiamine to grow in glucose medium with adenine (3)(4)(5).…”
Section: Resultsmentioning
confidence: 99%
“…Amino-4-imidazolecarboxamide ribotide (AICAR) is an intermediate in the de novo purine biosynthetic pathway and its accumulation impacts a variety of metabolic processes in a number of organisms such as Salmonella enterica (3)(4)(5)(6), Escherichia coli (8), Saccharomyces cerevisiae (9), and humans (11). AICAR is also generated as a by-product during histidine biosynthesis and recycled by subsequent entry into the purine biosynthetic pathway in organisms that synthesize histidine ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These activators and inhibitors interconvert the FBPase homotetramer between its active R state and inactive T state (25,57). Specific allosteric inhibitors of FBPase include AMP (51), glucose 6-phosphate (26), and 5-amino-4-imidazole carboxamide ribotide (AICAR) (21). Activators include phosphoenolpyruvate (PEP), citrate, and sulfate ions (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In S. enterica, the thiamine requirement of a purH mutant (Yura 1956;Newell and Tucker 1968;Downs 1987) and the inability of the same mutant to grow on glycerol (Burton 1971;Dougherty et al 2006) have been attributed to the accumulation of AICAR. In Rhizobium etli, genetic studies showed that AICAR accumulation affected cellular processes such as the production of the cytochrome terminal oxidase cbb 3 (Soberon et al 1997) and the infection stages of symbiosis (Newman et al 1994).…”
mentioning
confidence: 99%